Automating Software Compilation with The Gradle Tool Using the Example of a Lesson Planning System - Mateusz GÓRNIAK; Konrad HOLENDER; Paweł KACZMAREK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2022)
In this paper, the authors describe a solution for automating software compilation in Kotlin with a Gradle solution. The use of the Spring Framework and the tools described allows a system to be set up very quickly with an application server, e.g. for testing solutions, remote service invocation using the http protocol or REST API integration with a neural network written in any language that exposes REST API services.
Keywords: Gradle; software compilation; build software automating